Evaluation of force-time curve analysis methods in the isometric mid-thigh pull test - Liu, J.; Qu, X.; Stone, M. H. (Sports Biomechanics, 2023)
The purpose of this study was to evaluate the manual and automatic analysis methods for force-time curve analysis of the isometric mid-thigh pull (IMTP) test. The visual analysis, first derivative analysis and threshold analysis methods were used to analyse onset time and time-specific forces at 50 ms, 90 ms, 200 ms and 250 ms on the force-time curve. Ninety-three collegiate sports athletes' trials were selected and analysed by each method. The visual analysis method was set as the reference method for paired comparisons with the first derivative analysis method and threshold analysis method. Onset time comparisons revealed that the first derivative analysis method was comparable with the visual analysis method with average difference at about 30ms. Results from the weighted least products regression analysis and the Bland-Altman analysis showed that large fixed bias confounded by proportional bias existed in the threshold analysis method, and time-specific force variables obtained from the first derivative analysis method were closer to those from the visual analysis method when compared with the threshold analysis method. These findings suggest that the first derivative analysis method could be an effective tool for force-time curve analysis of the IMTP test.